Sleeping sickness is a circadian disorder - Filipa Rijo-Ferreira (Nature Portfolio, 2018)
African sleeping sickness is well known for the alterations of sleeping patterns, but it is not known how circadian biology is altered by the causative pathogen Trypanosoma brucei. Here the authors show T. brucei causes a disorder of the cellular circadian clock that is unrelated to the immune response to the parasite.